No evidence of Polyomavirus and EBV infections in Italian patients with mixed cryoglobulinemia infected chronically with HCV. - Comar, Manola; Zanotta, Nunzia; Del Savio, Rossella; Vascotto, Fulvia; Calabrese, Nadia; Zorat, Francesca; Pozzato, Gabriele (J Med Virol, 2014)
Mixed cryoglobulinemia is a lymphoproliferative disorder associated with hepatitis C virus (HCV). In patients chronically affected by HCV the prevalence of mixed cryoglobulinemia is variable ranging from 0% to 56%. To verify whether polyomaviruses (PyV) play a role in this disorder a total of 222 blood samples from 63 HCV chronic patients, 43 with mixed cryoglobulinemia, 59 chronic lymphocytic leukemia, 50 polytransfused patients, and 50 blood donors were evaluated for Merkel (MCPyV), BKV, JCV, and SV40. EBV was additionally included in the analysis since association with this disorder has been reported. Mixed cryoglobulinemia patients infected chronically with HCV resulted negative for both PyV and EBV. MCPyV was found in 1 subject with Merkel Cell Carcinoma, in 10% of polytransfused and in 10% of blood donors while EBV was detected in 22% of polytransfused, 10% of B-cell lymphatic leukemia patients and 4% of blood donors (P < 0.01). Taken together, the absence of PyV and EBV in HCV-mixed cryoglobulinemia patients seems to exclude a direct involvement of these viruses in the pathogenesis of this disease while the presence of MCPyV in healthy individuals, at the same rate as in polytransfused patients, may reinforce data on a minimal role of this virus in other human pathologies.
Keywords: Adult; Base Sequence; Cryoglobulinemia; DNA, Viral; Epstein-Barr Virus Infections; Female; Hepacivirus; Hepatitis C, Chronic; Herpesvirus 4, Human; Humans; Italy; Leukemia, B-Cell; Male; Middle Aged; Polyomavirus; Polyomavirus Infections; Sequence Analysis, DNA; Vaginal Smears; Young Adult